FRS651: Forensic Chemical Analysis / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2021)
This course gives the student a basic understanding of the theory and applications of the methods of modern analytical chemistry as applied to forensic problems. The lectures include the theory of operation of various instruments and the fundamental science on which they are based. Applications of these instruments to forensic samples will be introduced. Topics include drug analysis, arson investigation and the analysis of paint and inks. The outcomes shall be assessed through a variety of tools which include the final examination, tests and quizzes, laboratory reports and presentation of case study.